(untitled) (Health Renaissance, 2014)
Background: In addition to chronic pain and anxiety disorders, few studies have found promising role of gabapentin in relieving acute postoperative pain as well as acute anxiety too. Objectives: To evaluate the effect of gabapentin premedication on preoperative anxiety and postoperative pain in patients undergoing elective open cholecystectomy. Methods: A prospective, randomized, double blind and placebo controlled study. Eighty adult patients of ASA I and II were divided into 2 groups of 40 each. Patients in group 1 and group 2 received capsules Gabapentin (1200mg) or identical placebo capsules 2 hours prior to surgery respectively. Preoperative anxiety and 12 hours postoperative pain was assessed using Anxiety and Pain VAS score respectively along with the observation of side effects. Postoperatively, intravenous pethidine 0.5 mg/kg was given when pain VAS > 40mm and time to first pethidine injection and total pethidine consumption in 12 hours was recorded. Results: Anxiety VAS scores after one hour of drug intake (35.75±20.11 versus 46.63±12.73) and just before induction of anaesthesia (45.75±30.27versus 68.13±29.84) along with postoperative Pain VAS scores were significantly lower in gabapentin group. Time to the first pethidine demand was significantly longer (145.34±194.54 min versus 26.30±51.02min) and cumulative pethidine consumption throughout study period was also significantly lower (35.91 ± 16.61 versus 57.84 ± 20.72mg) in gabapentin group. Conclusions: 1200 mg gabapentin premedication in open cholecystectomy patients significantly reduced preoperative anxiety, postoperative pain and total pethidine consumption with negligible side effects. DOI: http://dx.doi.org/10.3126/hren.v11i3.9642 Health Renaissance 2013;11(3):254-259